Solar energy an income accelerating option for irrigation of Kinnow orchard: An example in Rajasthan state of India - MEENA, N K; SINGH, RAM; FEROZE, S M; JOLIYA, PRADEEP (The Indian Journal of Agricultural Sciences, 2021)
The PV solar device for pumping water from underground and from other source of water for irrigation has been recognized as very new initiative. Three year socio-economic study sponsored by Ministry of Human Resource under higher education scheme has been conducted in two districts of Rajasthan applying standard methodology to assess comparative advantages of PV solar device for irrigation of kinnow orchard. Hence, study found that solar irrigation system has enhanced the returns of farm and played a partial catalyst role to enhance the income of the farm. Therefore, the economic as well as environment benefits need to realize for popularization of the solar device for betterment of farming society which would reduce the dependency on electricity of farmers for irrigation specially and other works depend on electricity generally. Hence, provision of incentives on solar devices should be made to the farmers.